Hemodynamic Support with a Percutaneous Left Ventricular Assist Device during Stenting of an Unprotected Left Main Coronary Artery - Kar, Biswajit (2004)
Coronary artery bypass grafting prolongs survival in patients with left main coronary artery stenosis. However, this benefit is denied to patients who refuse the procedure or who are poor surgical candidates due to comorbid conditions. We describe a novel technique for the percutaneous revascularization of stenosis in an unprotected left main coronary artery in high-risk patients. The TandemHeart™, a percutaneously inserted left ventricular assist device, was used to provide periprocedural hemodynamic support during angioplasty and stenting of an unprotected left main coronary artery for stenosis in a 70-year-old woman. The device was removed immediately after the procedure, and the patient was discharged from the hospital on the 2nd postprocedural day. The potential advantages of angioplasty with the support of percutaneous left ventricular assist devices in high-risk patients are discussed.